Penggunaan Kafein Sitrat pada Bayi Prematur - Marsubrin, Putri Maharani Tristanita; Sugiyarto, Kanya Lalitya Jayanimitta (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Apnea is a manifestation of immature breathing and frequently occurs in preterm infants treated in the Neonatal Intensive Care Unit. Apnea of prematurity (AOP) is characterized by episodes of apnea (cessation of breathing) lasting 15–20 seconds or more, or shorter episodes accompanied by bradycardia and/or desaturation. The incidence of AOP is inversely related to gestational age (GA) and birth weight. Caffeine is one of the pharmacological treatments for managing AOP. Caffeine belongs to the methylxanthine class, like theophylline and aminophylline. Caffeine has been used as a therapy of choice for AOP in developed countries since the 1970s. Meanwhile, in developing countries, aminophylline remains the most commonly used drug for AOP management. Compared to aminophylline and theophylline, caffeine has better therapeutic effects and absorption, a longer half-life, and fewer side effects. Therefore, caffeine is the first-line therapy for AOP management.